Auditoría informática utilizando Benchmarking para los servidores del departamento de cómputo de la dirección provincial de salud de El Oro - Espinel Amores, Nancy Alexandra (2013)
This research focuses on the development of a software audit process to evaluate and determine the compliance leveled quality management of the data center of the Provincial Directorate of Health of El Oro, based on the ISO standard 19011. The process involves collection technique by applying two tools.